Changing Concepts of Work in Thailand - Baker, Simon; Hess, Michael (Journal of Comparative International Management)

(untitled) (Management Futures, 2001)
ABSTRACT Historically in Thai society 'work' has been defined broadly but recent economic changes have led to a narrowing of ideas about what constitutes work. The commodification of labour this entails is familiar from the history of economic change in many nations. This article seeks to go beyond re-stating the obvious parallels. In particular, because the specificities of these changes in each nation reveal underpinning attitudes to work, we believe that they have significance for understanding worker attitudes and therefore for decision making on both labour policy and management practice. Some Thais defining work will recite a 1950's slogan introduced by the military dictator Sarit that states 'ngan khu ngern, ngern khu ngan, banda suk', which means work is money, money is work and this brings us happiness. This article seeks an understanding of what this means in practice. It begins by looking generally at broad concepts of work and economic development. It then considers how this has impacted on language and normative values in other nations, and looks at how economic change in Thailand has led to a profound shift in attitudes to work. In particular attention is focused on the language used to describe work because this language is redolent of the process of cultural legitimisation by which working for money becomes normative. The article uses both Thai and Isarn (the name given to the dialect and region in Northeast Thailand) illustrations to show usage change in both urban and rural areas.